Bond characterization between concrete substrate and repairing SFRC using pull-off testing - Bonaldo, Everaldo (2005)
In the last years, an emerging repair and strengthening technique for concrete slabs has been used, consisting of applying a thin layer of steel fibre reinforced concrete(SFRC) onto the slabs. The performance of the strengthened structural system depends on the bonding behaviour between old and new concretes. Adhesives based on epoxy resins currently make this liaison. The prices of these adhesives are quite different depending, mainly, on the percentage of pure resin that they include. In the present paper, three commercial adhesive compounds of distinct prices and properties were selected to bond concrete substrate and repairing SFRC. The bond behaviour was assessed from pull-off tests and the influence of the strength class of concrete substrate and repairing SFRC was analysed. Finally, the performance of the adhesives was evaluated considering both the bond strength and their prices.